Rice Production without Insecticide in Smallholder Farmer's Field - Ali, M. P.; Bari, M. N.; Ahmed, N.; Kabir, M. M. M.; Afrin, S.; Zaman, M. A. U.; Haque, S. S.; Willers, J. L. (Frontiers in Environmental Science, 2017)
Highlights: Use of perching, sweeping, and need based insecticide (IPM technique) useage produce at par yields compared to prophylactic insecticide useage in rice fields. There exists a technique that can reduce 75% of insecticide useage in rice field. The results were obtained in cooperation between smallholder rice farmers and researchers of Bangladesh. Currently rice protection from insect pests solely depends on chemical pesticides which have tremendous impact on biodiversity, environment, animal, and human health. To reduce their impact from our society we need to cut pesticide use from agricultural practices. To address this issue, we did an experiment to identify realistic solutions that could help farmers build sustainable crop protection systems and minimize useage of insecticides and thus reduce the impact of pesticides in the environment. Innovations developed jointly by farmers and researchers and evaluated for their potential to be adopted by more farmers. In this paper we tested four management practices jointly with smallholder farmer fields in order to select the best one. Four management practices were used namely, T1 = Prophylactic use of insecticide where insecticide was applied in rice field at every 15 days interval without judging the infestation level; T2 = Perching (that is, placing roosting (perching) sites for insectivorous birds within the rice field) and concurrent sweep net samples along with need-based insecticide application; T3 = Perching only; and T4 = Farmer's own practices. The results revealed that routine application of insecticides for crop protection is not mandatory which is commonly found at use in rice farmers. In our experiment, where prophylactic method or farmers used 3–4 times insecticides without judging the insect pests infestation level, the similar pest population was found when compared to the field where insecticide was not applied. Our management system reduced by 75% the use of insecticides even if the field was infested with an insect pest. Predatory insects were higher in numbers than that of insecticide treated fields. We conclude farmers' should refrain insecticide applications up to 30–40 days after transplanting to enhance higher predatory arthropod population numbers, which might check pest populations in rice fields. Our experimental results show that a proper manner of an integrated pest management (IPM) cut pesticide use without any yield penalty. Results indicate the T2 management system minimizes pest damage by increasing natural enemies and can improve environmental quality.